Compensatory enhancement of paternal care in maternally neglected mice family - Jang, Jaewon; Kim, Hea-jin; Koh, Hae-Young (한국통합생물학회, 2023)
Parental care strategies, ranging from biparental to uniparental, evolve based on factors affecting sexual conflict over care. Plasticity in how parents respond to reduction in each other's care effort is thus proposed to be important in the evolution of parental care behaviors. Models predict that 'obligate' biparental care is stable when a parent responds to reduced partner effort with 'partial' compensation, trading-off current and future reproduction. A meta-analysis of experimental studies on biparental birds also revealed partial compensation, supporting coevolution of parental care type and plasticity pattern. However, few studies have addressed this issue across different taxa and different parental care types. In laboratory mice, a female-biased 'facultative' biparental species, fathers paired with a competent mother rarely provide care. We show that, when mated with a pup-neglecting mutant mother, fathers increased care effort to 'fully' compensate for the lost maternal care in both pup survival rate and total care amount. Pup retrieval latency was significantly shorter, and neural activity in relevant brain regions twice as high, suggesting enhanced motivation. This study with mice not only opens a road to explore the neural correlates of paternal plasticity but will also help understand how behavioral plasticity contributes to adaptive evolution of parental care behaviors.